Al-Qur’ān dan Ketahanan Keluarga: Studi Kasus di Lembaga Konsultasi Keluarga PERSISTRI (Persatuan Islam Istri) - Diah Hasanah (JOURNAL OF QUR'AN AND HADITH STUDIES, 2019)
Al-Qur’ān has provided an ideal family description which is categorized as having to fulfill the elements of sakīnah, mawaddah, and rahmah. Therefore, the idea of family resilience emerged as a response to existing family problems. The changing era from time to time has been influencing the concept and practice of ideal family. This transformation brings about either negative or positive impact to family live. This became the Persistri's motivation to participate in overcoming family problems while maintaining and applying the teachings of the Qur’ān. The purpose of this study is to explore the Persistri's way of overcoming family problems and to explore the concept of family resilience in the version of the Persistri which is based on the verses of the Qur’ān. The research method used is qualitative with data collection based on the results of interviews and observations. This study finds that the existence of the Persistri is helpfull for societies, especially its members in dealing with family problem, the role of persistri in this case lies in its participation in streghtening the resilience of family, in which it is expected by Muslims and the government.